Skillnad mellan versioner av "1.5a Lösning 6b"

Från Mathonline
Hoppa till: navigering, sök
m
m
Rad 1: Rad 1:
 +
:<math>\begin{align} {1+x \over 1}  & = {1 \over x}                        & | \;\; -1        \\
 +
                        \sqrt{6 x + 10}    & = x - 1                      & | \;  (\;\;\;)^2 \\
 +
                              6 x + 10      & = (x - 1)^2                                      \\
 +
                              6 x + 10      & = x^2 - 2 x + 1  \qquad\qquad & |  - 10        \\
 +
                              6 x          & = x^2 - 2 x - 9  \qquad\qquad & |  - 6 x        \\
 +
                                          0 & = x^2 - 8 x - 9                                  \\
 +
    \end{align}</math>
 +
 
:<math>\begin{align}    {1+x \over 1}  & = {1 \over x}          \\
 
:<math>\begin{align}    {1+x \over 1}  & = {1 \over x}          \\
  

Versionen från 14 juli 2014 kl. 16.33

\[\begin{align} {1+x \over 1} & = {1 \over x} & | \;\; -1 \\ \sqrt{6 x + 10} & = x - 1 & | \; (\;\;\;)^2 \\ 6 x + 10 & = (x - 1)^2 \\ 6 x + 10 & = x^2 - 2 x + 1 \qquad\qquad & | - 10 \\ 6 x & = x^2 - 2 x - 9 \qquad\qquad & | - 6 x \\ 0 & = x^2 - 8 x - 9 \\ \end{align}\]

\[\begin{align} {1+x \over 1} & = {1 \over x} \\ x^2 - 8 x - 9 & = 0 \\ x_{1,2} & = 4 \pm \sqrt{16 + 9} \\ x_{1,2} & = 4 \pm 5 \\ x_1 & = 9 \\ x_2 & = - 1 \\ \end{align}\]